(untitled) (Eureka Journal of Humanities and Social Research, 2026)
The article examines the institution of invalidation of the debtor’s transactions as one of the central legal mechanisms for protecting the property rights of creditors in insolvency proceedings under the law of the Republic of Uzbekistan. Drawing on the Law of the Republic of Uzbekistan No. ZRU–763 of 12 April 2022 “On Insolvency”, the Civil Code, and the Economic Procedural Code, the author analyses the grounds, terms (so-called “suspect periods”), procedural framework, and legal consequences of declaring the debtor’s pre-insolvency transactions invalid. Particular attention is given to Chapter 6 of the Insolvency Law (Articles 63–68), which differentiates between transactions causing losses to creditors, transactions involving preferential satisfaction, and transactions concluded with the debtor’s successors. The article identifies systemic problems in law enforcement practice and offers proposals for further development of the doctrine and legislation.